RESEARCH OF KHOREZM LITERARY SOURCES - NARGIZA ?ADAMBAEVNA ADAMBAEVA (International Journal of Innovations in Engineering Research and Technology, 2021)
In this article the sources of the Khorezm oasis are widely covered, and soon, along with the economy and culture, the Khorezm shopping centers, especially the part of it that was part of the Golden Horde state (after the Mongol invasion, Khorezm was divided into North Khorezm and South Khorezm, part of the Chigatay Nation). The resurgence of cities is widely covered.